2017
DOI: 10.1016/j.ccell.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hematopoietic Cell Kinase Activity Suppresses Myeloid Cell-Mediated Colon Cancer Progression

Abstract: SUMMARY Aberrant activation of the SRC family kinase hematopoietic cell kinase (HCK) triggers hematological malignancies as a tumor cell-intrinsic oncogene. Here we find that high HCK levels correlate with reduced survival of colorectal cancer patients. Likewise, increased Hck activity in mice promotes the growth of endogenous colonic malignancies and of human colorectal cancer cell xenografts. Furthermore, tumor-associated macrophages of the corresponding tumors show a pronounced alternatively activated endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 74 publications
5
82
0
Order By: Relevance
“…The finding that there was an increased risk of Gastric Cancers in high IL-10 producer haplotype was in agreement with the concept that Th2 cytokines including IL-10 are highly expressed in patients with Gastric Cancers as was shown in our study results and This idea could partially be clarified by reported findings that increased expression of mRNA and raised serum levels of IL-10 are correlated with the progression of Gastric Cancers (15,(36)(37) . Similar results recently have been reported in patients with different histotypes of solid and hematopoietic tumors suggesting that IL-10 overproduction may be a communal survival strategy of several types of human malignancies (38) . Also keeping in mind that inflammatory cells may be less frequent within metastases than in primary lesions, it is likely that the main source of IL-10 may be the tumor itself rather than the inflammatory infiltrates (39) .…”
Section: Discussionsupporting
confidence: 87%
“…The finding that there was an increased risk of Gastric Cancers in high IL-10 producer haplotype was in agreement with the concept that Th2 cytokines including IL-10 are highly expressed in patients with Gastric Cancers as was shown in our study results and This idea could partially be clarified by reported findings that increased expression of mRNA and raised serum levels of IL-10 are correlated with the progression of Gastric Cancers (15,(36)(37) . Similar results recently have been reported in patients with different histotypes of solid and hematopoietic tumors suggesting that IL-10 overproduction may be a communal survival strategy of several types of human malignancies (38) . Also keeping in mind that inflammatory cells may be less frequent within metastases than in primary lesions, it is likely that the main source of IL-10 may be the tumor itself rather than the inflammatory infiltrates (39) .…”
Section: Discussionsupporting
confidence: 87%
“…FLT3-ITD mutation failed to transform primary hematopoietic progenitor cells from CDK6-deficient mice, pointing at CDK6 as the prime target of CDK4/6 inhibitors in AML [93]. FLT3-ITD increases CDK6 expression through activation of the v-Src sarcoma (Schmidt-Ruppin A-2) viral oncogene homolog (SRC)-family kinase hemopoietic cell kinase (HCK) (Figure 4); for both kinases approved selective drugs are available for the clinic [33][34][35][36]94]. The combination of compounds targeting the FLT3-HCK-CDK6 axis with classical chemotherapeutics may thus represent a rational strategy for clinical trials in FLT3-ITD + AML.…”
Section: Cdk6 Blockage Attacks Flt3-driven Aml Via Several Roadsmentioning
confidence: 99%
“…Furthermore, expression of SFKs on myeloid cells is associated with poor prognosis and a pro-tumour M2-like macrophage endotype 21 . However, there is little data regarding individual SFK expression within the tumour cells and their impact on patient survival and clinical response in CRC.…”
Section: Introductionmentioning
confidence: 99%